Circuit theory: analysis and synthesis - Chakrabarti, A (Dhanpat Rai & Co, 2008)
Circuit theory: analysis and synthesis / Chakrabarti, A. -- New Delhi: Dhanpat Rai & Co., 2008 621.3192 C426e5 5th rev ed No. of Copies : 1